GASTROESOPHAGEAL REFLUX DISEASE AMONG CHILDREN AS A RISK FACTOR FOR ESOPHAGUS ADENOCARCINOMA - N.V. Gerasimova; A.V. Myzin; S.V. Bel'mer; S.A. Polyudov; V.P. Nazhimov ("Paediatrician" Publishers LLC, 2006)
Within recent years, pediatricians have paid special attention to gastroesophageal reflux disease in relation to the risk of the metaplastic changes of mucous coat of esophagus. Intestinal metaplasia is an essential risk factor for the growth of esophagus adenocarcinoma. According to our data, diseases of the lower third of esophagus and Z-line were observed among almost 6% of patients, who underwent endoscopic examination. In the research, where 109 children with protractedly nonhealing defects of the lower third of esophagus and Z-line were involved, the authors uncovered intestinal metaplasia among 26 children (23,85%) and Gastral metaplasia among 24 children (22,02%). To clarify the character of the changes in the mucous coat of the lower third of esophagus, there was a research on esophagi of 32 deceased children aged between 6 months and 15 years old (deceased with neither gastroenterological pathology to be diagnosed when alive, nor implications of gastroesophageal reflux). In 4 cases, in the distal esophagus under the multilayered scaly epithelium the researchers discovered segments of the enteral epithelium. Some medications were noted to cause perforation of the intestinal epithelium by the enteral epithelium with its emergence onto the surface. We should not ignore the fact that a risk factor for intestinal metaplasia can be the congenital focuses of ectopia of the intestinal epithelium in the mucous coat of esophagus. Key words: mucous coat of esophagus, barrett's syndrome, intestinal metaplasia, esophagus adenocarcinoma, Н. pilori, inesophageal РH-metrics, children.